Cover Image, Volume 22, Issue 10. Issue 10 (7th September 2020) - Svane, Maria S.; Johannesen, Helle H.; Martinussen, Christoffer; Bojsen‐Møller, Kirstine N.; Hansen, Martin Lundsgaard; Hansen, Adam E.; Deacon, Carolyn F.; Hartmann, Bolette; Keller, Sune H.; Klausen, Thomas L.; Loft, Annika; Kjaer, Andreas; et al.
Abstract : The cover image is based on the Original Article No effects of a six‐week intervention with glucagon‐like peptide‐1 receptor analogue on pancreatic volume and edema in obese men without diabetes by JOHAN LÖFGREN et al., https://doi.org/10.1111/dom.14106 .